Effective carbonaceous desiccated coconut waste adsorbent for application of heavy metal uptakes by adsorption: Equilibrium, kinetic and thermodynamics analysis - Abdul Rahim, A.R. (Elsevier Ltd, 2020)
The char desiccated coconut adsorbent (DCWC) is prepared through a facile carbonization method in an open-air muffle furnace. The characterization analyses of the adsorbents show that the carbonized adsorbent has more significant pore structure, higher surface area and higher composition of elemental carbon all while retaining the same functional group as the pristine adsorbent. Among the carbonized adsorbent, surface area of DCWC500 is 134.640 m2/g, the highest among the carbonized adsorbent i.e. DCWC400 and DCWC300. The carbonization of the desiccated coconut waste materials resulted in higher adsorption capacity of the adsorbent where the recorded maximum monolayer capacity was 2.65 and 3.51 mmol/g for DCWP and DCWC500, respectively. The adsorptive uptake of Pb(II) by the adsorbents follows Langmuir isotherm and pseudo-second order kinetic model which indicates the process follows favourable monolayer adsorption process governed by chemical adsorption. Both DCWP and DCWC500 adsorbents are regenerable up to five (5) adsorption-desorption cycles of Pb(II) with the ability to retain Pb(II) removal above 85. In respect to its application for Pb(II) removal in wastewater, both DCWP and DCWC performed a highly effective Pb(II) removal which indicate that the adsorbents are potential as an efficient and cost-friendly adsorbent alternatives for industrial application. Â© 2020